KEARIFAN LOKAL MASYARAKAT MADURA DALAM NOVEL SILSILAH DUKA KARYA DWI RATIH RAMADHANY - Meliani Risdiana; Eggy Fajar Andalas (Kajian Linguistik dan Sastra, 2022)
Local wisdom is part of a long journey of efforts to preserve culture or customs that have an influence and position that is rooted in people's lives. The purpose of this research is to describe the form and position of local wisdom in the life of Madurese people in the novel Silsilah Duka by Dwi Ratih Ramadhany. In answering this problem the Anthropology of Literature approach is used with the  Stuart Hall Representation theory. This research uses qualitative research with the source of data of Silsilah Duka novel by Dwi Ratih Ramadhany and used data in the form of narratives, thoughts, and actions taken by the characters in the novels of Griefs that contain forms of local wisdom and illustrates how local wisdom positions in the life of the Madurese community. The data collection technique used in the study is the note-taking technique. Data analysis techniques include data presentation, data reduction and conclusion drawing. The results of this study indicate that in the novel there is a form of local wisdom in the form of beliefs including the abstinence of pregnant women touching sea water, the myths of hunger, abstinence of pregnant women eating squid, to the danger of children not drinking herbal medicine and Festivals or Traditions including Traditions for distribution of fat starch or Rose-pote and Tradition for the dead. The position of local wisdom in community life in social and religious aspects has a strong role and influence in regulating the life structure of Madurese people and protecting people's lives despite the pros and cons regarding the view of local wisdom, namely strong belief in local wisdom, local wisdom by the elderly and the weakening of belief in local Madurese wisdom by young people.